2017
DOI: 10.1590/s0100-204x2017000500005
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus forms in leaves and their relationships with must composition and yield in grapevines

Abstract: -The objective of this work was to evaluate phosphorus forms in grape leaves and their relationships with must composition and yield in grapevines grown in a Typic Hapludalf with different available P contents. Two experiments were carried out with Vitis vinifera cultivars, one with 'Tannat' and the other with 'Cabernet Franc' grapes. Experiment 1 consisted of two vineyards of 'Tannat', with the following P content in the soil: V1, 11.8 mg kg -1 P; and V2, 34.6 mg kg -1 P. Experiment 2 consisted of two vineyar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…For this cultivar, there was a decreasing trend in total titratable acidity and tartaric acid concentration with increasing P rates, but an increasing one in pH, with significant differences only in 2011/2012. This behavioral trend in pH and total titratable acidity values was also observed by Piccin et al (2017a) for the 'Tannat' and 'Cabernet Franc' grapevines (V. vinifera), with significant differences. These results are most likely due to the greater P movement in the plant at flowering and veraison, as shown by the increase in leaf P concentration with increasing P rates applied to the soil (Table 2).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…For this cultivar, there was a decreasing trend in total titratable acidity and tartaric acid concentration with increasing P rates, but an increasing one in pH, with significant differences only in 2011/2012. This behavioral trend in pH and total titratable acidity values was also observed by Piccin et al (2017a) for the 'Tannat' and 'Cabernet Franc' grapevines (V. vinifera), with significant differences. These results are most likely due to the greater P movement in the plant at flowering and veraison, as shown by the increase in leaf P concentration with increasing P rates applied to the soil (Table 2).…”
Section: Resultssupporting
confidence: 68%
“…The decrease in total titratable acidity was 0.24 meq L -1 for each kilogram of P 2 O 5 applied to the soil; however, the decrease in tartaric acid in the must was only 0.002 meq L -1 for each kilogram of P 2 O 5 applied. This behavior was also shown in the data collected by Piccin et al (2017a), who did not identify a significant variation in the soluble solids contents, pH, and total titratable acidity of the studied grapes. However, these authors found important variations in phenolic composition -especially in total polyphenols and total anthocyanins -in relation to the P rates applied to the vineyard.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…However, viticulture involves fertilizer application: in Brazil, for instance, nearly 44% of the expenses are utilized for soil amendments such as acidity correctives accounting around 13% for the total cost of vineyard maintenance and production (>4 years) (IEG/FNP, 2017). Therefore, the fertilizer application must be monitored and used only when needed, and in judicious doses, to raise the soil nutrient availability necessary to maintain the requisite nutritional status (Ciotta et al, 2016) and to ensure a high quality and compensatory harvest (Piccin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%